Effects of carbamide on fluidity and setting time of sulphoaluminate cement and properties of planting concrete from sulphoaluminate cement. (10th September 2018) - Gong, Chenchen; Zhou, Xiangming; Dai, Wenyan; Liu, Yu; Lu, Lingchao; Cheng, Xin
Graphical abstract: Highlights: Carbamide increased setting and fluidity of SAC and was released slowly in concrete. With the increase of carbamide amount to 2.5 wt.% the permeability coefficient of SAC-based planting concrete caused by fluidity of paste increased to 23.2 mm/s which was 21.5% higher than that without carbamide. With the increase of the amount of carbamide the release amounts and cumulative release rates of nitrogen nutrients increased, which led to alkalinity and compressive strength of planting concrete decreased. Abstract: In this paper carbamide as the fertilizer was added into planting concrete. As carbonic acid was produced during carbamide hydrolysis the fluidity and setting time of sulphoaluminate cement (SAC) was studied to investigate its effects on properties of cement. Its effects on compressive strength, water permeability coefficient, alkalinity and nitrogen release of concrete and stem length of plants were studied to evaluate the adaptability of SAC concrete for plant growth. Results revealed that carbamide extended the initial and final setting time of SAC paste and increased its fluidity because carbamide was soluble in water and carbonate ion produced from carbamide dissolution reacted with calcium ion from cement hydration. Subsequently calcium carbonate was formed which covered the surface of unhydrated cement grains so that prohibited their hydration. With the increase of carbamide amount to 2.5 wt% the permeability coefficient of SAC-based planting concrete caused by fluidity of paste increased to 23.2 mm/s which was 21.5% higher than that without carbamide. With the increase of the amount of carbamide the release amounts and cumulative release rates of nitrogen nutrient increased, leading to decreasing in both alkalinity and compressive strength of planting concrete. With the increase of curing age compressive strength of planting concrete increased and alkalinity reduced stably, which was desirable. At 14 and 21 days after budding with the increase of carbamide content, stem lengths had a trend to increase and were obviously greater than that in concrete without carbamide, which was in good correspondence to release rate of nitrogen nutrient from planting concrete.